Efficacy of fluralaner spot-on solution against induced infestations with Rhipicephalus sanguineus on dogs - Taenzler, Janina (Parasit Vectors, 2016)
BACKGROUND: The efficacy of fluralaner spot-on solution administered once topically against induced infestations with Rhipicephalus sanguineus was evaluated in dogs over a 12-week post-treatment period. METHODS: Six negative-controlled studies were conducted, involving a total of 112 adult dogs (57 mixed breed, 47 Beagles, eight Labradors). In each study, dogs were randomized to two groups of eight to ten dogs each. On day 0, dogs in each treated group were topically administered fluralaner spot-on solution once at a dose of 25 mg/kg body weight, while dogs in each control group were not treated. Two days before treatment, and on days 28, 56 and 84 after treatment, all dogs were infested with approximately 50 unfed, adult Rh. sanguineus ticks (sex ratio 1:1). Ticks were removed and counted on days 2, 30 (4 weeks), 58 (8 weeks), and 86 (12 weeks) after treatment to assess efficacy. RESULTS: Efficacy against ticks 2 days after treatment was 91.1 % (study 1), 98.4 % (study 2), 100 % (study 3), 97.6 % (study 4), 99.6 % (study 5), and 99.8 % (study 6). At all other assessment time points, tick efficacy was 95.4–100 %. Tick reduction in all treatment groups was significant at all assessment time points (P < 0.0001). CONCLUSIONS: A single topical administration of fluralaner spot-on solution provides a high level of therapeutic and persistent efficacy against Rh. sanguineus ticks over the subsequent 12 weeks.